Ideational Meta-Function Meaning Perspective in Jane Eyre’s Novel - Sofiani, Yulia; Somba, Sugianti; Ramadhianti, Agustina (Kajian Linguistik dan Sastra, 2025)
Based on Michael Halliday's Systemic Functional Linguistics (SFL) theory, this study examines the meaning of Charlotte Brontë's Jane Eyre from the standpoint of ideational meta-function. The way that ideas and experiences are expressed in language, particularly through the contexts, participants, and processes in the text, is reflected in the ideational meta-function. To explain the character dynamics and the novel's primary themes—such as freedom, gender equality, morality, and emotional conflict, this research points out the utilization of material, mental, and relational processes in the main dialogues. The analysis's findings demonstrate that, particularly in discourses that emphasize women's social constraints, relational mechanisms tend to be applied to character identity and social positions. The introspection of the main character, such as Jane's contemplation of her autonomy and self-worth, is exhibited through mental processes. Material processes, on the other hand, show the characters' tangible responses to different difficulties. Furthermore, the novel's ideological meaning is reinforced by the circumstances, including comparison and periodicity. Abstrak Berdasarkan teori Linguistik Fungsional Sistemik (SFL) Michael Halliday, penelitian ini meneliti makna Jane Eyre karya Charlotte Brontë dari sudut pandang metafungsi ideasional. Cara ide dan pengalaman diekspresikan dalam bahasa, khususnya melalui konteks, partisipan, dan proses dalam teks, tercermin dalam metafungsi ideasional. Untuk menjelaskan dinamika karakter dan tema utama novel—seperti kebebasan, kesetaraan gender, moralitas, dan konflik emosional, penelitian ini menunjukkan pemanfaatan proses material, mental, dan relasional dalam dialog utama. Temuan analisis menunjukkan bahwa, khususnya dalam wacana yang menekankan kendala sosial perempuan, mekanisme relasional cenderung diterapkan pada identitas karakter dan posisi sosial. Introspeksi karakter utama, seperti perenungan Jane tentang otonomi dan harga dirinya, ditunjukkan melalui proses mental. Proses material, di sisi lain, menunjukkan respons nyata karakter terhadap berbagai kesulitan. Lebih jauh lagi, makna ideologis novel tersebut diperkuat oleh keadaan-keadaan, termasuk perbandingan dan periodisasi